Personalized immunization to optimize vaccine immunogenicity: exploring the multidimensional effects of host intrinsic factors, external intervention strategies, and the external environment - Chen, Keda; Gu, Siyi; Li, Jiaxuan; Xu, Yutong; Wang, Zhiyi; Zhang, Yanjun; Li, Jianhua (Frontiers in Immunology, 2025)
Vaccines are a fundamental tool in the prevention and control of infectious diseases; however, significant individual variability in immunogenicity exists. This variability is not solely attributable to vaccine characteristics but is also influenced by a range of factors. This review systematically examines the key factors influencing vaccine immunogenicity, with particular emphasis on host-intrinsic factors (e.g., metabolic status, genetic background), personalized external interventions, such as optimized vaccine delivery techniques (e.g., aspiration-based skin delivery) and immunomodulatory adjuvant therapies (e.g., acupuncture, moxibustion, and near-infrared light therapy), as well as environmental exposures and immune memory. By examining the mechanisms and recent research advancements associated with these factors, this paper seeks to provide a foundation for the development of personalized vaccination strategies to address future public health challenges.